Time delay anisotropy in photoelectron emission from isotropic helium. (August 2015) - Heuser, S; Jiménez-Gálan, Á; Cirelli, C; Sabbar, M; Boge, R; Lucchini, M; Gallmann, L; Ivanov, I; Kheifets, A; Dahlström, J M; Lindroth, E; Argenti, L; et al.
Synopsis: In contrast to expectations, we observe that the photoionization time delay from the 1 s 2 spherically symmetric ground state of He depend on the electron emission direction with respect to an external reference. We attribute the observed anisotropy to the interplay between different final quantum states, which become accessible once two photons are involved in the photoionization process. This is a universal effect, which needs to be taken into account for any study dealing with photoionization dynamics.